2014
DOI: 10.1177/0022343313510014
|View full text |Cite
|
Sign up to set email alerts
|

How naming and shaming affects human rights perceptions in the shamed country

Abstract: Although individual citizens perceive the human rights conditions in their country differently, existing research on human rights and public opinion has tended to ignore the possible impact from international sources of information. This article builds upon previous research on human rights, public opinion, and international organizations by arguing that citizens will perceive the human rights conditions in their country more negatively when their country is shamed by the international community for human righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…As grievances grow, this will "empower and legitimate the claims of domestic opposition groups against norm-violating governments" (Risse et al, 1999, p. 5), mobilizing them against the regime. Davis and colleagues (2012) and Ausderan (2014) demonstrate that, cross-nationally, foreign shaming does indeed make a country's citizens less likely to believe their government respects human rights the following year. 7 Powerful repressive and censorship apparatuses mean that authoritarian regimes like the CCP can exert strong control over this information.…”
Section: Authoritarian States and Foreign Pressurementioning
confidence: 99%
“…As grievances grow, this will "empower and legitimate the claims of domestic opposition groups against norm-violating governments" (Risse et al, 1999, p. 5), mobilizing them against the regime. Davis and colleagues (2012) and Ausderan (2014) demonstrate that, cross-nationally, foreign shaming does indeed make a country's citizens less likely to believe their government respects human rights the following year. 7 Powerful repressive and censorship apparatuses mean that authoritarian regimes like the CCP can exert strong control over this information.…”
Section: Authoritarian States and Foreign Pressurementioning
confidence: 99%
“…A rich IR literature examines the use and efficacy of a variety of naming and shaming instruments, ranging from formal resolutions, blacklists, and targeted sanctions to discursive representations that impose reputational costs such as social opprobrium on targets. While states are adept users of naming and shaming as documented in this literature (Ausderan, ; Biersteker, ; de Goede, ; Lebovic & Voeten, ), a robust scholarship centers on its use by nonstate actors (NSAs), particularly nongovernmental organizations (NGOs), in the arena of human rights (Bell & Carens, ; Bob, ; Hill, Moore, & Mukherjee, ; Keck & Sikkink, ; Meernik, Aloisi, Sowell, & Nichols, ; Murdie & Peksen, ; Ron, Ramos, & Rodgers, ). Despite the centrality accorded to NGOs in promulgating human rights norms through naming and shaming, the literature provides a rudimentary understanding of their underlying motivations, assessment, and conceptualization of this tool.…”
Section: The Emotional Diplomacy Of Ngos: Bringing Nonstate Actors Bamentioning
confidence: 99%
“…One mechanism by which INGO "shaming and blaming" campaigns can induce policy change is by influencing public opinion on human rights conditions (Davis, Murdie and Steinmetz, 2012;Ausderan, 2014). Recent research has found that shaming reports alone, even without changes zations.…”
Section: The Influence Of Human Rights Ingo Shaming On Aid Delivery Tmentioning
confidence: 99%
“…in actual human rights conditions, is associated with changes in public opinion (Davis, Murdie and Steinmetz, 2012;Ausderan, 2014). Further, according to recent World Value Survey reports, ordinary citizens are more confident of NGOs than of their government or the media.…”
Section: The Influence Of Human Rights Ingo Shaming On Aid Delivery Tmentioning
confidence: 99%